Endothelial Progenitor Cells for Ischemic Stroke: Update on Basic Research and Application. (16th August 2017) - Liao, Shaohua; Luo, Chunxia; Cao, Bingzhen; Hu, Huaiqiang; Wang, Suxia; Yue, Huili; Chen, Lin; Zhou, Zhenhua
Abstract : Ischemic stroke is one of the leading causes of human death and disability worldwide. So far, ultra-early thrombolytic therapy is the most effective treatment. However, most patients still live with varying degrees of neurological dysfunction due to its narrow therapeutic time window. It has been confirmed in many studies that endothelial progenitor cells (EPCs), as a kind of adult stem cells, can protect the neurovascular unit by repairing the vascular endothelium and its secretory function, which contribute to the recovery of neurological function after an ischemic stroke. This paper reviews the basic researches and clinical trials of EPCs especially in the field of ischemic stroke and addresses the combination of EPC application with new technologies, including neurovascular intervention, synthetic particles, cytokines, and EPC modification, with the aim of shedding some light on the application of EPCs in treating ischemic stroke in the future.